INTERPRETASI LAPISAN BAWAH PERMUKAAN DENGAN MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DAN GEOKIMIA: STUDI KASUS TPA MUARA FAJAR RUMBAI - Alifia Putri Yasmin; Juandi M (Universitas Riau, 2021)
The need for water daily is a big problem for people living around Muara Fajar Final Processing Place (TPA) – Rumbai. This study aims to identify the depth of subsurface structures around the Muara Fajar landfill area using the Schlumberger configuration dielectric method and determine the water quality in the community wells around the landfill site. The data obtained in the acquisition process are used to calculate the apparent resistivity value at each measurement point and analyzed quantitatively and qualitatively. Then proceed with the inversion process using the progress program so that obtained resistivity value and layer thickness at each point of measurement. The results of measurement inline 1 get a range of resistivity values ranging from 961.19 – 2.10 Ωm and line 2 of 109.31 – 31.15 Ωm. Underground water taken is residents well water in the research area as many as 5 sample points using GPS. This underground water sample will be tested with parameters such as pH, TDS, Conductivity, Salinity, and Turbidity. Underground water cannot be consumed from the results of the water quality test with the parameters mentioned at the beginning if referring to the Regulation of the Minister of Health of the Republic of Indonesia because the pH obtained in all underground water samples is < 6.5 or acidic, the value of the conductivity exceeds the quality standard, and high dominant salinity value. As for the TDS and Turbidity parameters, the values are by the quality standard.